1992
DOI: 10.1192/bjp.161.6.791
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Iron Status and Chronic Akathisia in an In-patient Population with Chronic Schizophrenia

Abstract: Iron status and akathisia were assessed in 105 long-stay in-patients who fulfilled DSM-III-R criteria for schizophrenia, all but three of whom were receiving antipsychotic medication. Chronic akathisia was diagnosed in 23% and pseudoakathisia in 20%. No significant correlation was found between serum iron concentration and the severity of akathisia. There was no significant difference in serum iron concentration between patients with chronic akathisia and those without. However, serum iron and percentage satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…Several authors have found decreased serum iron in patients suffering from akathisia (Barnes & Braude, 1985;Brown et al, 1987), but others (Nemes et al, 1991;Barnes et al, 1992) did not replicate this finding. All of these studies assayed morning serum iron only.…”
mentioning
confidence: 56%
“…Several authors have found decreased serum iron in patients suffering from akathisia (Barnes & Braude, 1985;Brown et al, 1987), but others (Nemes et al, 1991;Barnes et al, 1992) did not replicate this finding. All of these studies assayed morning serum iron only.…”
mentioning
confidence: 56%
“…Some evidence suggests a role for iron deficiency in chronic and tardive akathisia, which is associated with reduced dopamine activity due to the use of dopamine antagonists. Results from previous studies investigating the association between akathisia and iron deficiency in patients with psychosis have been inconsistent; in patients with chronic psychotic disorders, akathisia was found to be associated with decreased plasma ferritin and iron levels [ 23 , 24 , 25 , 26 , 27 ], whereas no association between iron indices and akathisia was observed in other studies of chronic and acute akathisia [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 97%
“…Für Olanzapin wurden in ersten Studien 7%, für Sertindol Werte zwischen 5 und 10% gefunden (Beasley et al, 1996;Dunn u. Fitton, 1996;Street et al, 1996;Zimbroff et al, 1996). Auch Quetiapine ruft vermutlich seltener eine Akathisie hervor (Wetzel et al, 1995) al., 1994) und der Pseudoakathisie zwischen 18 und 41 %( Barnes et al, 1992;Brown u. White, 1991;Halstead et al, 1994;Munetz u. Cornes, 1982) (Tab.…”
Section: Prävalenz/lnzidenzunclassified